Tackling sexually transmitted infection burden in Ugandan communities living in the United Kingdom: a qualitative analysis of the socio-cultural interpretation of disease and condom use - Atukunda, Esther Cathyln; Mugyenyi, Godfrey Rwambuka; Oloro, Joseph; Hughes, Skye (African Health Sciences, 2015)
Background: Despite being in a different country and social environment, Ugandans living in the UK still reportedly have the lowest rates of condom usage and one of the highest incidences of STIs in UK. In Uganda, STIs and HIV prevalence has been reported to be on the increase. Understanding peoples’ beliefs and the attitudes that influence their behavior is a key factor to effectively designing control programs. Methods: A qualitative study that interviewed 37 purposively selected Ugandans living in the UK was conducted. Lay theories and interpretations were derived using thematic analysis. Results: Condoms generally carried a lot of stigma and were perceived for use primarily in extramarital affairs and pregnancy control. HIV/AIDS was most feared due to its perceived socio-psychological or physical effects unlike other STIs described as “non-threatening” due to wide availability of “quality” treatment in UK. Notions of trust, the purpose of relationships, symptom recognition and partner selection greatly influenced decisions to undertake consistent condom use. Conclusions: The socio-cultural understanding of STIs, sex, trust and relationships are symbolic in influencing consistent condom use among Ugandans. This indicates a need to acknowledge community beliefs and values about sexual health and design messages about STIs and condoms that would help eliminate these serious condom-related misconceptions.
Keywords: Sexually transmitted infection; Ugandan communities; Socio-cultural interpretation; Disease and condom use